A toolbox for a structured risk-based prehabilitation program in major surgical oncology - Sliwinski, Svenja; Werneburg, Elisabeth; Faqar-Uz-Zaman, Sara Fatima; Detemble, Charlotte; Dreilich, Julia; Mohr, Lisa; Zmuc, Dora; Beyer, Katharina; Bechstein, Wolf O.; Herrle, Florian; Malkomes, Patrizia; Reissfelder, Christoph; et al. (Frontiers in Surgery, 2023)
Prehabilitation is a multimodal concept to improve functional capability prior to surgery, so that the patients’ resilience is strengthened to withstand any peri- and postoperative comorbidity. It covers physical activities, nutrition, and psychosocial wellbeing. The literature is heterogeneous in outcomes and definitions. In this scoping review, class 1 and 2 evidence was included to identify seven main aspects of prehabilitation for the treatment pathway: (i) risk assessment, (ii) FITT (frequency, interventions, time, type of exercise) principles of prehabilitation exercise, (iii) outcome measures, (iv) nutrition, (v) patient blood management, (vi) mental wellbeing, and (vii) economic potential. Recommendations include the risk of tumor progression due to delay of surgery. Patients undergoing prehabilitation should perceive risk assessment by structured, quantifiable, and validated tools like Risk Analysis Index, Charlson Comorbidity Index (CCI), American Society of Anesthesiology Score, or Eastern Co-operative Oncology Group scoring. Assessments should be repeated to quantify its effects. The most common types of exercise include breathing exercises and moderate- to high-intensity interval protocols. The program should have a duration of 3–6 weeks with 3–4 exercises per week that take 30–60 min. The 6-Minute Walking Testing is a valid and resource-saving tool to assess changes in aerobic capacity. Long-term assessment should include standardized outcome measurements (overall survival, 90-day survival, Dindo–Clavien/CCI®) to monitor the potential of up to 50% less morbidity. Finally, individual cost-revenue assessment can help assess health economics, confirming the hypothetic saving of 8 for treatment for 1 spent for prehabilitation. These recommendations should serve as a toolbox to generate hypotheses, discussion, and systematic approaches to develop clinical prehabilitation standards.